Readiness of Biology Education Lecturers to Conduct E-Learning During the Covid-19 Pandemic - I Ketut Surata; I Gede Sudirgayasa; I Made Sudiana; I Made Maduriana (Universitas Pendidikan Ganesha, 2020)
The purpose of this study is to find out: (1) the readiness qualifications of lecturers doing e-learning in general; (2) qualification of lecturer's e-learning readiness based on readiness factor; (3) qualification of lecturer's readiness based on his birth generation. This research method uses a quantitative descriptive approach, with readiness assessment using the Aydin & Tasci Scale. The respondents were 21 lecturers of private colleges Biology Education in the Bali Region. The results showed: (1) lecturer readiness qualifications for e-learning are generally in the ready category, but need a slight improvement; (2) lecturer's e-learning readiness qualification based on readiness factor entered category is not ready, requires a slight improvement in financial readiness and technological readiness factor. Ready, but it takes a little improvement in sociological readiness, environmental readiness, human resource readiness, and equipment readiness. Ready, this e-learning implementation factor can be continued in psychological readiness and content readiness; and (3) qualifications for lecturer readiness based on their birth generation are in the ready category but need a slight improvement, with the highest readiness score in the baby boomer generation.